Desarrollo de un modelo didáctico de aprendizaje basado en problemas y el uso de laboratorios virtuales en la asignatura de educación cultural y artística del segundo año BGU paralelo “D” de la Unidad Educativa Pedro Vicente Maldonado periodo 2021-2022 - María de los Ángeles, Basantes Baños (2023)
ABSTRACT: When analyzing the needs within the national educational system, the importance of including teaching techniques and didactic strategies aimed at students in the teaching-learning process was evidenced, therefore, the purpose of this research was to develop a didactic model of Problem-Based Learning and the use of Virtual Laboratories in the subject of Cultural and Artistic Education. The didactic model was characterized by the use of innovative methodologies such as the resolution of daily life problems posed to the students, which were developed through a virtual medium that contained a section called "Virtual Laboratory" which allowed students to have material and information necessary to solve the different activities that allowed solutions to the initial problem; the student in this process became the main objective of the class to seek their own knowledge. The investigation yielded data from the application of two evaluations; an initial evaluation addressed to the students who are part of the study, from which academic information and knowledge of the students was obtained in reference to the topics already worked on in the subject of Cultural and Artistic Education under a traditional model; The second evaluation was applied once the proposed didactic model was developed, this allowed us to know if its application improved the knowledge acquired. In the final evaluation, the students demonstrated through their qualifications the level of knowledge reached after the proposal, the statistical analysis compared the results obtained in the two evaluations and it was determined that the problem-based learning model through the use of virtual laboratories was striking and interesting; as well as the data determined that the didactic proposal was beneficial in the teaching-learning process because there was a marked difference in the pre and post proposal results with 37.15% of students who obtained grades less than or equal to 7 before applying the proposal, once it was applied the percentage increased, reaching very satisfactory grades, from 11.49% initially to 51% after the proposal. Keywords: Didactic model, problem-based learning, virtual laboratories.